Identification of mouse mammary tumor virus-specific mRNA. - Groner, B (1979)
Complementary DNA corresponding to the RNA genome of mouse mammary tumor virus was used to identify viral RNA contained in polysomes of a virus-producing mammary tumor cell line. Separation of polysomal mRNA by agarose gel electrophoresis, transfer of the RNA to diazobenzyloxymethyl paper, and hybridization with 32P-labeled mouse mammary tumor virus complementary DNA revealed three viral RNA size classes of 10, 8.8, and 4.4 kilobases in length, respectively.